Battery

By applying active material layers with different impedances on the arc and straight areas of the positive electrode sheet of the lithium-ion battery, the negative electrode over-embedding problem caused by excessive positive electrode performance during the fast charging of the lithium-ion battery is solved, and the cycle stability and safety of the battery are significantly improved.

CN119890403AActive Publication Date: 2025-04-25ZHUHAI COSMX BATTERY CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411982925.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-31
Publication Date
2025-04-25
Estimated Expiration
2044-12-31

AI Technical Summary

Technical Problem

During the fast charging process, lithium-ion batteries are prone to over-embedding of the negative electrode due to excessive positive electrode, causing the battery to have an increase in the battery's cyclic expansion rate and even short circuits and fires, which affects the battery's cycle life and safety.

Method used

The first active material layer and the second active material layer are coated on the arc area and the straight area of ​​the positive electrode sheet by using partition coating technology. By adjusting the impedance of the coating, the electrode impedance and strength of the positive electrode sheet are improved, thereby matching the negative electrode area and reducing the risk of swelling and rupture of the lithium-ion battery.

Benefits of technology

It effectively reduces the bulging and rupture problem in the arc area of ​​lithium-ion batteries, improves the cycle stability and safety of the battery, and extends the service life of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119890403A_ABST
    Figure CN119890403A_ABST
Patent Text Reader

Abstract

The invention provides a battery which comprises an electrode assembly of a winding structure, the electrode assembly comprises a negative plate, a diaphragm and a positive plate which are sequentially stacked and wound, the electrode assembly comprises an arc area and a straight area connected with the arc area, the positive plate comprises a positive current collector, the positive current collector is provided with a main body area and a passivation area in the length direction, and the main body area and the passivation area are arranged in the arc area. The passivation region is located in the arc region, and the main body region is located in the straight region; at least one side surface of the positive current collector in the main body region comprises a first active material layer, and at least one side surface of the positive current collector in the passivation region comprises a second active material layer; the impedance of the first active material layer is smaller than that of the second active material layer. According to the battery provided by the invention, cyclic expansion caused by over-embedding of the negative electrode due to excessive exertion of the positive electrode in the circular arc area of the winding battery can be effectively reduced, so that the problem of bulging and cracking at the circular arc of the lithium ion battery is effectively solved, and the cyclic stability and the safety of the battery are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of energy storage, and in particular to a battery. Background Art

[0002] As the global trend of energy conservation and emission reduction develops, the dependence on fossil fuels is reduced, and green energy emerges, lithium-ion battery (LIB) technology has become very important. LIBs are the most widely used batteries in portable electronics, electric vehicles, power tools, and various grid applications because of their high power and energy density, low cost, and better life cycle. Since the energy density of LIBs is mainly determined by their output voltage and specific capacity, this makes the electrode a very important component. The electrode assembly of LIBs consists of active materials and current collectors, which have a large surface area for electrochemical processes during the charge and discharge cycle. In order to meet the rapidly growing customer needs in the electronics industry, further performance development of LIBs in terms of fast charging is essential.

[0003] Most researchers focus on improving the active material properties and chemical composition of the electrode, reducing the electrode thickness and reducing the mass load (the amount of active material per unit area). However, these methods do not produce a very obvious improvement effect on the rapid swelling of the battery under fast charging, especially the arc of the wound structure battery often causes the negative electrode to be over-embedded due to excessive positive electrode development, which can easily cause the battery's cycle expansion rate to continue to rise, and the battery arc will swell severely, resulting in battery capacity attenuation, and even short circuit and fire. Therefore, it seriously affects the cycle life and safety of high-rate charge and discharge lithium-ion batteries. Summary of the invention

[0004] Based on the above problems, the present invention provides a battery that can effectively reduce the cyclic expansion caused by over-embedding of the negative electrode due to excessive positive electrode development in the arc area of ​​the wound battery, thereby effectively improving the swelling and rupture problem at the arc of the lithium-ion battery, enhancing the battery's cyclic stability and improving the battery's safety.

[0005] To achieve the above purpose, the technical solution adopted by the present invention is as follows:

[0006] A first aspect of the present invention provides an electrode sheet, comprising an electrode assembly of a winding structure, wherein the electrode assembly comprises a negative electrode sheet, a separator and a positive electrode sheet which are stacked and wound in sequence, wherein the electrode assembly comprises an arc region and a straight region connected to the arc region, wherein the positive electrode sheet comprises a positive electrode current collector, wherein the positive electrode current collector is provided with a main region and a passivation region along a length direction, wherein the passivation region is located in the arc region, and the main region is located in the straight region;

[0007] At least one side surface of the positive electrode current collector located in the main region includes a first active material layer, and at least one side surface of the positive electrode current collector located in the passivation region includes a second active material layer;

[0008] The impedance of the first active material layer is smaller than the impedance of the second active material layer.

[0009] Through the above technical solution, the present invention has at least the following advantages compared with the prior art:

[0010] The battery of the present invention adopts a zoned coating technology in the arc area and the straight area of ​​the electrode assembly with a winding structure formed by winding, so that the impedance of the first active material coating in the main area located in the straight area of ​​the positive electrode collector is smaller than the impedance of the second active material coating in the passivation area located in the arc area of ​​the current collector, thereby effectively improving the electrode impedance and electrode strength at a specific position of the positive electrode sheet, so that the passivated positive electrode sheet can better match the negative electrode area that is prone to lithium plating swelling, thereby effectively improving the arc swelling and rupture of the lithium-ion battery caused by excessive lithium insertion of the negative electrode arc, and at the same time alleviating the deformation and cracking of the battery cell caused by stress concentration in the arc area of ​​the battery cell during subsequent use, thereby improving the cycle stability of the battery and improving the safety of the battery.

[0011] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article. BRIEF DESCRIPTION OF THE DRAWINGS

[0012] Figure 1 A schematic cross-sectional view of an electrode assembly with a jellyroll structure provided in one embodiment of the present invention;

[0013] Figure 2 A schematic top view of a positive electrode sheet structure with a tab disposed in the middle provided in an example of the present invention;

[0014] Figure 3 A schematic top view of a positive electrode sheet structure with multiple tabs provided in an example of the present invention;

[0015] Figure 4 A schematic top view of a positive electrode sheet structure of a conventional electrode tab provided in an example of the present invention;

[0016] Figure 5 The cross-sectional SEM morphology image of the first active material layer and the cross-sectional SEM morphology image of the second active material layer of the positive electrode sheet in one example of the present invention;

[0017] Figure 6 This is a planar SEM morphology image of the second active material layer of the positive electrode sheet in an example of the present invention.

[0018] Description of reference numerals:

[0019] 1-main area, 11-main area, 2-passivation area, 21-passivation area, 3-ear, 4-empty foil area. DETAILED DESCRIPTION

[0020] The specific embodiments of the present invention are described in detail below. It should be understood that the specific embodiments described herein are only used to illustrate and explain the present invention, and are not used to limit the present invention.

[0021] A first aspect of the present invention provides a battery, such as Figure 1 As shown, it is a cross-sectional schematic diagram of an electrode assembly with a core structure provided in an example of the present invention; the battery includes an electrode assembly with a wound structure, the electrode assembly includes a negative electrode sheet, a separator and a positive electrode sheet stacked and wound in sequence, the electrode assembly includes an arc region 2 and a straight region 1 connected to the arc region 2, the positive electrode sheet includes a positive electrode collector, and the positive electrode collector is provided with a main region 11 and a passivation region 21 along the length direction, the passivation region 21 is located in the arc region 2, and the main region 11 is located in the straight region 1; when the above-mentioned electrode assembly with a wound structure is unfolded, the main region 11 and the passivation region 21 are alternately arranged along the length direction of the positive electrode collector according to the structural characteristics of the wound battery cell, as shown in FIG. Figure 2 As shown, Figure 2 The diagram is a top view of a positive electrode sheet structure with a tab disposed therein provided in an example of the present invention.

[0022] like Figure 2 , 3 As shown in , at least one side surface of the positive electrode current collector located in the main area 11 includes a first active material layer, and at least one side surface of the positive electrode current collector located in the passivation area 21 includes a second active material layer; the impedance of the first active material layer is less than the impedance of the second active material layer. The impedance of the first active material layer is less than the impedance of the second active material layer, which is equivalent to passivating the positive electrode current collector area where the second active material layer is located, thereby forming a passivation area with a larger impedance, and the impedance of the positive electrode current collector area that has not been passivated is smaller, which is the main area.

[0023] Conventional technology does not passivate the arc of the positive electrode sheet. During the winding process, the CB value of the arc where the convex side of the negative electrode corresponds to the concave side of the positive electrode (in the same stage and under the same conditions, the negative electrode capacity on the opposite side exceeds the margin of the positive electrode capacity, CB value = negative electrode active material gram capacity × negative electrode surface density × negative electrode active material content ratio ÷ (positive electrode active material gram capacity × positive electrode surface density × positive electrode active material content ratio)) is reduced. During the charge and discharge process, the insufficient local CB value will lead to the transition of lithium insertion in the negative electrode arc in the corresponding area, causing the battery arc to swell and the electrode to break, seriously affecting the long cycle performance and safety performance of the lithium-ion battery. Therefore, the positive electrode sheet of the present invention adopts a zoned coating technology in the arc area and non-arc area (straight area) of the winding core formed by winding, so that the impedance of the first active material coating located in the non-arc area of ​​the positive current collector can be made smaller than the impedance of the second active material coating located in the arc area of ​​the current collector, that is, the active coating located in the arc area of ​​the electrode sheet is passivated, which can effectively improve the electrode impedance and electrode strength at a specific position, so that the passivated positive electrode sheet can better match the negative electrode area that is prone to lithium plating bulging, and reduce the lithium insertion SOC (SOC represents the charging state, the ratio of the current remaining power Qc to the total capacity Qn when it is fully charged, SOC = (Qc / Qn) × 100%) on the negative electrode side, thereby improving the bulging and rupture of the lithium-ion battery arc caused by the transitional lithium insertion of the negative electrode arc, and at the same time alleviate the deformation and cracking of the battery cell due to stress concentration in the arc area during subsequent use, thereby improving the battery cycle stability and improving the battery safety.

[0024] In the present invention, if Figure 2 , 3 As shown in FIG. 4 , the passivation region 21 includes N 钝 Sub-passivation area, N 钝 = the total number of arcs of the electrode assembly winding structure formed by the positive electrode sheet, that is, the number of sub-passivation zones included in the passivation zone of the positive electrode collector depends on the total number of arcs of the arc zones of the electrode assembly winding structure formed by the positive electrode sheet, and the main area 11 has arc zones on both sides along the winding direction of the electrode assembly, therefore, N 钝 The value of is actually equal to the sum of the number of arcs on both sides of the electrode assembly; however, it should be noted that the arc area only represents the division of a specific area on the electrode assembly, and does not mean that all of the specific areas are passivation areas or all require passivation.

[0025] In a specific embodiment, at least one side surface of the positive electrode current collector located in the sub-passivation zone includes the second active material layer, or at least one side surface of the positive electrode current collector located in the sub-passivation zone includes the first active material layer and the second active material layer. There are a large number of sub-passivation zones, and the sub-passivation zone that needs to be passivated includes the second active material layer or includes the first active material layer and the second active material layer at the same time, and the sub-passivation zone that does not need to be passivated includes the first active material layer in accordance with the main zone; in addition, when the sub-passivation zone includes the first active material layer and the second active material layer at the same time, the first active material layer and the second active material layer are arranged in sequence along the length direction of the positive electrode current collector, and are not stacked. It can be understood that N 钝 The second active material layer is not necessarily fully coated in each sub-passivation zone, and the first active material layer and the second active material layer may be coated simultaneously in some sub-passivation zones, so that the impedance of the positive electrode collector surface coating in the arc zone can be smaller than the impedance of the positive electrode collector surface coating in the straight zone, thereby effectively improving the arc bulging and rupture of the lithium-ion battery caused by excessive lithium insertion in the negative electrode arc, thereby enhancing the battery's cycle stability and improving the battery's safety.

[0026] In a specific embodiment, Figure 2 , 3 As shown in 4, in any one of the sub-passivation areas, along the length direction of the positive electrode current collector, the length of the second active material layer is L, the circumference of the arc formed by the sub-passivation area corresponding to the second active material layer is C, and the L and C satisfy 1 / 3*C≤L≤1 / 2*C; that is, the length L of the second active material layer is 1 / 3 to 1 / 2 of the circumference C of the whole circle completed by the arc area formed by the winding structure of the electrode assembly formed by winding the sub-passivation area corresponding to the second active material layer.

[0027] In a specific embodiment, Figure 2 As shown, along the width direction of the positive electrode current collector, the width of the second active material layer is D 活 , the width of the positive electrode sheet is D 极 , the D 活 and D 极 , satisfying D 活 ≤D 极 That is, the second active material layer can be fully coated in the width direction of the positive electrode current collector. 活 =D 极 , or not fully coated, then D 活 <D 极 .

[0028] In a specific embodiment, Figure 1As shown, along the length direction of the positive electrode current collector, the distance between adjacent second active material layers is I, and the width of the straight area is D 平 , the width of the arc area is D 圆 , the I and D 平 and D 圆 , satisfying 0≤(ID 平 ) / D 圆 ≤1. The width of the second active material layer coating area in the passivation zone along the length direction of the positive electrode current collector can be equal to the width of the passivation zone along the length direction of the positive electrode current collector, or it can be less than the width of the passivation zone along the length direction of the positive electrode current collector, that is, the passivation zone can be not fully coated in the length direction. Therefore, the spacing I between adjacent second active material layers will be greater than or equal to the width of the straight area along the length direction of the positive electrode current collector, and less than or equal to the width of the straight area along the length direction of the positive electrode current collector plus the width of the arc area along the length direction of the positive electrode current collector, so the I, D 平 and D 圆 , satisfying 0≤(ID 平 ) / D 圆 ≤1. In addition, it should be noted that when the passivation region is not fully coated in the length direction, the positive electrode current collector of the remaining width in the passivation region needs to be provided with the first active material layer.

[0029] In a specific embodiment, the coverage area of ​​the second active material layer on the surface of the positive electrode current collector accounts for 3%-20% of the total area of ​​the positive electrode current collector, for example, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14%, 15%, 16%, 17%, 18%, 19%, 20%. When the area of ​​the second active material layer is too large, the actual capacity of the battery cannot be exerted, the rate performance of the battery deteriorates, and the capacity decreases; when the area of ​​the second active material layer is too small, the problem of bulging and rupture at the arc cannot be well improved, affecting the cycle and safety performance of the battery.

[0030] In a preferred embodiment, the coverage area of ​​the second active material layer on the surface of the positive electrode current collector accounts for 3%-8% of the total area of ​​the positive electrode current collector.

[0031] In the present invention, the first active material layer and the second active material layer may include a positive electrode active material, a binder and a conductive agent; the mass content ratio of the binder to the conductive agent in the first active material layer is a1, 0.5≤a1≤2, for example, 0.5, 0.6, 0.7, 0.8, 0.9, 1, 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, 1.9, 2; the mass content ratio of the binder to the conductive agent in the second active material layer is a2, 1.5≤a2≤6, for example, 1.5, 1.6, 1.7, 1.8, 1.9, 2, 3, 4, 5, 6.

[0032] In a specific embodiment, 0.13≤a1 / a2≤0.6, for example, 0.13, 0.14, 0.15, 0.16, 0.17, 0.18, 0.19, 0.2, 0.21, 0.22, 0.23, 0.24, 0.25, 0.26, 0.27, 0.28, 0.29, 0.3, 0.31, 0.32, 0.33, 0.34, 0.35, 0.36, 0.37, 0.38, 0.39, 0.4, 0.41, 0.42, 0.43, 0.44, 0.45, 0.46, 0.47, 0.48, 0.49, 0.5, 0.55, 0.6.

[0033] The present invention simultaneously adjusts the content relationship of the conductive agent and the binder in the first active material layer and the second active material layer to satisfy 0.5≤a1≤2 and / or 1.5≤a2≤6, and further satisfies 0.13≤a1 / a2≤0.6; it will not affect any electrical properties of the battery, but can also significantly reduce the problem of material shedding in the passivation zone of the electrode during winding, significantly increase the flexibility of the arc pole piece, significantly reduce the amount of lithium embedded in the arc during full charging, significantly reduce the expansion rate of the negative electrode at the arc, and thus alleviate the expansion force of the arc zone, thereby avoiding the problem of arc breakage, arc lithium precipitation, and significant thickness increase caused by excessive lithium embedding and expansion of the arc, and further improving the cycle stability and safety of the lithium-ion battery.

[0034] In a preferred embodiment, 0.7≤a1≤1.5.

[0035] In a preferred embodiment, 1.9≤a2≤5.

[0036] In a preferred embodiment, 0.2≤a1 / a2≤0.5.

[0037] In a specific embodiment, the positive electrode active material includes lithium transition metal oxide and / or lithium-containing phosphate.

[0038] In a specific embodiment, the lithium transition metal oxide includes at least one of lithium cobalt oxide, lithium nickel oxide, lithium manganese oxide, lithium nickel cobalt oxide, lithium manganese cobalt oxide, lithium nickel manganese oxide, lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide and modified compounds thereof.

[0039] In a specific embodiment, the lithium-containing phosphate includes at least one of lithium iron phosphate, a composite material of lithium iron phosphate and carbon, lithium manganese phosphate, a composite material of lithium manganese phosphate and carbon, lithium iron manganese phosphate, a composite material of lithium iron manganese phosphate and carbon, and modified compounds thereof.

[0040] In a specific embodiment, the binder includes at least one of polyvinylidene fluoride, styrene-butadiene rubber, and aluminate coupling agent.

[0041] In a specific embodiment, the conductive agent includes at least one of superconducting carbon, acetylene black, carbon black, carbon dots, carbon nanotubes, graphene and carbon nanofibers.

[0042] In a specific embodiment, the mass content of the positive electrode active material in the second active material layer is 90wt%-98wt%, for example, 90wt%, 91wt%, 92wt%, 93wt%, 94wt%, 95wt%, 96wt%, 97wt%, 98wt%; the mass content of the binder in the second active material layer is 2wt%-10wt%, for example, 2wt%, 3wt%, 4wt%, 5wt%, 6wt%, 7wt%, 8wt%, 9wt%, 10wt%; the mass content of the conductive agent in the second active material layer is 0.1wt%-1wt%, for example, 0.1wt%, 0.2wt%, 0.3wt%, 0.4wt%, 0.5wt%, 0.6wt%, 0.7wt%, 0.8wt%, 0.9wt%, 1wt%.

[0043] In a specific embodiment, the mass content of the positive electrode active material in the first active material layer is 90wt%-98wt%, for example, 90wt%, 91wt%, 92wt%, 93wt%, 94wt%, 95wt%, 96wt%, 97wt%, 98wt%; the mass content of the binder in the first active material layer is 1wt%-5wt%, for example, 1wt%, 2wt%, 3wt%, 4wt%, 5wt%; the mass content of the conductive agent in the first active material layer is 0.5wt%-5wt%, for example, 0.1wt%, 0.2wt%, 0.3wt%, 0.4wt%, 0.5wt%, 0.6wt%, 0.7wt%, 0.8wt%, 0.9wt%, 1wt%, 1.5wt%, 2wt%, 2.5wt%, 3wt%, 3.5wt%, 4wt%, 4.5wt%, 5wt%.

[0044] The present invention can increase the difficulty of lithium removal in the passivation zone at the positive electrode arc and improve the strength of the positive electrode arc by reducing the usage amount of the conductive agent in the second active material layer and increasing the usage amount of the binder, thereby reducing the conductivity of the second active material layer material and increasing the impedance of the second active material layer material in the passivation zone, so that the impedance of the second active material layer is greater than the impedance of the first active material layer, thereby improving the reaction rate of the active material material in the sensitive area corresponding to the arc by local passivation modification. When the value is within this range, the expansion stress of the arc zone during charging and discharging will be significantly lower than that of the central core zone, which can effectively alleviate the problem of electrolyte exhalation caused by stress extrusion of the arc. After further arc stress reduction, the problem of electron transmission obstruction caused by arc shedding and fragmentation can be effectively alleviated, thereby significantly improving the safety and cycle stability of lithium batteries.

[0045] In the present invention, the first active material layer may include a positive electrode active material, a binder and a conductive agent, and the second active material layer may include an active material, a filler, a binder and a conductive agent. In the second case, a filler may be added to the second active material layer as a passivation modifier of the active material material in the passivation zone to reduce the impedance of the second active material layer.

[0046] In a specific embodiment, the filler includes inorganic particles, and the inorganic particles include at least one of oxide ceramics, nitride ceramics, and carbide ceramics.

[0047] In a specific embodiment, the oxide ceramic includes at least one of aluminum oxide, titanium oxide, calcium oxide, chromium oxide, zinc oxide, zirconium oxide, and silicon oxide.

[0048] In a specific embodiment, the nitride ceramic includes at least one of silicon nitride, boron nitride, aluminum nitride, and gallium nitride.

[0049] In a specific embodiment, the carbide ceramic includes at least one of titanium carbide, tungsten carbide, and silicon carbide.

[0050] In a specific embodiment, the positive electrode active material is a ternary material or a lithium cobalt oxide material, and the filler includes a lithium-containing phosphate; the lithium-containing phosphate includes at least one of lithium iron phosphate, lithium manganese phosphate, lithium manganese iron phosphate, lithium manganese oxide, and lithium titanate.

[0051] The present invention can increase the impedance of the positive electrode passivation zone by adding fillers to the active materials, so that the impedance of the second active material layer in the positive electrode passivation zone is increased, the positive electrode reaction rate is reduced, and the capacity utilization of the negative electrode is reduced, thereby significantly improving the electrolyte storage capacity of the passivation zone. During the cycle process, especially in the late cycle, the electrolyte content in the arc region is significantly increased, and arc lithium plating caused by insufficient arc electrolyte due to stress extrusion is prevented, thereby improving the cycle stability and safety of the lithium-ion battery.

[0052] In a specific embodiment, the Dv50 particle size of the inorganic particles is 0.5 μm-30 μm, for example, 0.5 μm, 1 μm, 1.5 μm, 2 μm, 2.5 μm, 3 μm, 3.5 μm, 4 μm, 4.5 μm, 5 μm, 6 μm, 7 μm, 8 μm, 9 μm, 10 μm, 11 μm, 12 μm, 13 μm, 14 μm, 15 μm, 16 μm, 17 μm, 18 μm, 19 μm, 20 μm, 21 μm, 22 μm, 23 μm, 24 μm, 25 μm, 26 μm, 27 μm, 28 μm, 29 μm, 30 μm. If the Dv50 particle size of the filler is too large, the capacity of the active material layer will be seriously reduced. In a preferred embodiment, the Dv50 particle size of the inorganic particles is 0.5 μm-5 μm.

[0053] In a specific embodiment, the Dv50 particle size of the positive electrode active material is 10 μm-19 μm, for example, 10 μm, 11 μm, 12 μm, 13 μm, 14 μm, 15 μm, 16 μm, 17 μm, 18 μm, or 19 μm.

[0054] In a specific embodiment, the ratio of the Dv50 particle size of the inorganic particles to the Dv50 particle size of the positive electrode active material is 0.05-1, for example, 0.05, 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, or 1.

[0055] When the particle size of the filler is within the above range, the specific surface area of ​​the positive second active material layer in the passivation zone can be significantly improved, and the particle size ratio of the inorganic particles to the active material particles can be further controlled, which can significantly improve the liquid retention capacity of the positive electrode active material particles at the arc, thereby reducing the problem of lithium precipitation caused by insufficient electrolyte in the arc during long-term circulation, and improving the long cycle performance of lithium-ion batteries.

[0056] In a specific embodiment, the ratio of the mass content of the filler in the second active material layer to the mass content of the positive electrode active material in the second active material layer is 0.01-0.11, for example, 0.01, 0.02, 0.03, 0.04, 0.05, 0.06, 0.07, 0.08, 0.09, 0.1, 0.11. Too much filler in the second active material layer will lead to excessive positive electrode impedance, and excessive positive electrode impedance will cause the arc positive electrode to be unable to function and deteriorate arc lithium deposition.

[0057] In a preferred embodiment, the ratio of the mass content of the filler in the second active material layer to the mass content of the positive electrode active material in the second active material layer is 0.02-0.1.

[0058] In a specific embodiment, the mass content of the positive electrode active material in the second active material layer is 90wt%-97wt%, for example, 90wt%, 91wt%, 92wt%, 93wt%, 94wt%, 95wt%, 96wt%, 97wt%; the mass content of the filler in the second active material layer is 1wt%-11wt%, for example, 1wt%, 2wt%, 3wt%, 4wt%, 5wt%, 6wt%, 7wt%, 8wt%, 9wt%, 10wt%, 11wt%; the mass content of the binder in the second active material layer is 1wt%-5wt%, for example, 1wt%, 2wt%, 3wt%, 4wt%, 5wt%; the mass content of the conductive agent in the second active material layer is 0.5wt%-5wt%, for example, 0.5wt%, 1wt%, 1.5wt%, 2wt%, 2.5wt%, 3wt%, 3.5wt%, 4wt%, 4.5wt%, 5wt%.

[0059] In a preferred embodiment, the mass content of the filler in the second active material layer is 2wt%-10wt%.

[0060] In a specific embodiment, the mass content of the positive electrode active material in the first active material layer is 90wt%-98wt%, for example, 90wt%, 91wt%, 92wt%, 93wt%, 94wt%, 95wt%, 96wt%, 97wt%, 98wt%; the mass content of the binder in the first active material layer is 1wt%-5wt%, for example, 1wt%, 2wt%, 3wt%, 4wt%, 5wt%; the mass content of the conductive agent in the first active material layer is 0.5wt%-5wt%, for example, 0.1wt%, 0.2wt%, 0.3wt%, 0.4wt%, 0.5wt%, 0.6wt%, 0.7wt%, 0.8wt%, 0.9wt%, 1wt%, 1.5wt%, 2wt%, 2.5wt%, 3wt%, 3.5wt%, 4wt%, 4.5wt%, 5wt%.

[0061] In a specific embodiment, the ratio of the specific surface area of ​​the second active material layer to the specific surface area of ​​the first active material layer is 3-10, for example, 3, 4, 5, 6, 7, 8, 9, 10. The specific surface area of ​​the first active material layer and the second active material layer refers to the specific surface area of ​​the particulate material in the active material layer measured by BET analysis instrument. The specific operation steps are to load a certain amount of sample into the sample tube, and a certain amount of inert gas is introduced into the sample in a liquid nitrogen environment. The instrument calculates the specific surface area of ​​the material according to the amount of inert gas adsorbed.

[0062] In a preferred embodiment, the ratio of the specific surface area of ​​the second active material layer to the specific surface area of ​​the first active material layer is 3-6.

[0063] In one specific embodiment, the specific surface area of ​​the first active material layer is 0.1 m 2 / g-0.3m 2 / g, for example 0.1m 2 / g, 0.12m 2 / g, 0.13m 2 / g, 0.14m 2 / g, 0.15m 2 / g, 0.2m 2 / g, 0.25m 2 / g, 0.3m 2 / g; the specific surface area of ​​the second active material layer is 0.5m 2 / g-3m 2 / g, for example 0.5m 2 / g, 1m 2 / g, 1.5m 2 / g, 2m 2 / g, 2.5m 2 / g, 3m 2 / g.

[0064] In a preferred embodiment, the specific surface area of ​​the first active material layer is 0.15 m 2 / g-0.25m 2 / g.

[0065] In a preferred embodiment, the specific surface area of ​​the second active material layer is 0.7 m 2 / g-1.5m 2 / g.

[0066] The larger the specific surface area of ​​the second active material layer, the easier it is to store electrolyte. During the cycle, especially in the late cycle, it can significantly increase the electrolyte content in the arc area, prevent arc lithium plating caused by insufficient arc electrolyte due to stress extrusion, and thus improve the cycle stability and safety of lithium-ion batteries; however, the specific surface area of ​​the second active material layer should not be too much, because when the specific surface area of ​​the second active material layer is too large, it means that the lower the particle size of the filler material, the porosity of the positive electrode active material material will be significantly reduced, and the pore impedance of the positive electrode active material material will be increased. In severe cases, it is easy to cause negative electrode lithium precipitation, affecting the cycle performance of the battery. Therefore, it is necessary to regulate the specific surface area of ​​the second active material layer within an appropriate range.

[0067] In the present invention, the first positive electrode active material layer and the second positive electrode active material layer contain doping elements, and the doping elements include at least one of Al, Mg, Ti, and Zr.

[0068] In a preferred embodiment, in the first active material layer, the doping elements include Al, Mg, Ti and Zr, the doping amount of Al element is 1000ppm-5000ppm (for example: 1000ppm, 2000ppm, 3000ppm, 4000ppm, 5000ppm), and the doping amount of Mg element is 600ppm-2000ppm (for example: 600ppm, 700ppm, 800ppm, 900ppm, 1000ppm, 1100ppm, 1200ppm, 1300ppm, 1400ppm, 1500ppm, 1600ppm, 1700ppm, 1800ppm). pm, 1900ppm, 2000ppm), the doping amount of Ti element is 600ppm-2000ppm (for example: 600ppm, 700ppm, 800ppm, 900ppm, 1000ppm, 1100ppm, 1200ppm, 1300ppm, 1400ppm, 1500ppm, 1600ppm, 1700ppm, 1800ppm, 1900ppm, 2000ppm), and the doping amount of Zr element is 500ppm-1000ppm (for example: 500ppm, 600ppm, 700ppm, 800ppm, 900ppm, 1000ppm).

[0069] In a preferred embodiment, in the second active material layer, the doping elements include Al, Mg, Ti and Zr, the doping amount of Al element is 500ppm-2000ppm (for example: 500ppm, 600ppm, 700ppm, 800ppm, 900ppm, 1000ppm, 1100ppm, 1200ppm, 1300ppm, 1400ppm, 1500ppm, 1600ppm, 1700ppm, 1800ppm, 1900ppm, 2000ppm), the doping amount of Mg element is 20 The doping amount of Ti element is 100ppm-500ppm (for example: 100ppm, 200ppm, 300ppm, 400ppm, 500ppm, 600ppm, 700ppm, 800ppm, 900ppm, 1000ppm), the doping amount of Zr element is 100ppm-500ppm (for example: 100ppm, 200ppm, 300ppm, 400ppm, 500ppm).

[0070] The doping amounts of all doping elements in the above-mentioned active coatings can be measured by ICP doping element metal content test.

[0071] In a preferred embodiment, the doping amount of the doping element in the second active material layer is reduced by 10%-50% compared with the doping amount of the doping element in the first active material layer, for example, 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50%.

[0072] The present invention can improve the delithiation resistance of the positive electrode active material and reduce the delithiation amount of the positive electrode material by reducing the doping amount of doping elements such as Al in the second active material layer, thereby reducing the reaction rate of the positive electrode in the passivation area and reducing the capacity of the negative electrode, thereby improving the cycle stability of the lithium ion battery.

[0073] The present invention also provides a method for preparing a positive electrode sheet, wherein the second active material layer slurry after the above passivation is coated on a foil together with the first active material layer slurry according to a preset frequency and surface density to form the positive electrode sheet of the present invention. Specifically, the ratio of the second active material layer slurry and the first active material layer slurry after the above passivation is as described above and will not be repeated here. The solvent is added according to actual needs. For example, if the solid content is 40%, 60 parts of solvent are required for every 100 parts of slurry, and NMP is usually used as the solvent. The above materials are placed in a mixing tank, stirred thoroughly and filtered to obtain the first active material layer slurry, and the first active material layer slurry and the second active material layer slurry in the passivation zone are placed in two coating feeding tanks respectively. The feeding system draws two materials into the double-layer coating die according to the feeding setting parameters. The first coating die extrude the first active material layer slurry according to the set frequency and speed. The second coating die extrude the second active material layer slurry in the passivation area according to the set frequency and speed. The two slurries are mixed at the die lip and evenly coated on the first surface and / or the second surface of the current collector to form the positive electrode sheet of the present invention described above.

[0074] The preparation method of the positive electrode sheet of the present invention adopts a double-layer partition coating technology, which can adjust the extrusion frequency and speed of the two slurries, and efficiently realize local coating of the passivation zone, thereby reducing the reaction rate of the passivation zone, reducing the negative electrode arc lithium insertion SOC, and improving the cycle performance of the lithium-ion battery.

[0075] The tab 3 of the positive electrode sheet of the present invention may be a tab-centered structure (eg Figure 2 As shown), multi-electrode structure (such as Figure 3 as shown) or conventional tab structure (as shown Figure 4 As shown), an empty foil area 4 is also provided on one side of the positive electrode sheet along the length direction of the positive electrode current collector, as shown Figure 2 , 3 , as shown in Figure 4.

[0076] In the present invention, the electrode assembly includes a negative electrode sheet, a separator and a positive electrode sheet which are stacked and wound in sequence; the negative electrode sheet can be prepared according to conventional methods in the art. For example, an optional conductive agent, an optional binder, and an optional negative electrode active material are added to a solvent and stirred to form a uniform negative electrode active material slurry; the negative electrode active material slurry is coated on the first and / or second surface of the negative electrode current collector, and the negative electrode sheet is obtained by drying and cold pressing. Alternatively, the tabs can be welded or laser-cut at the position of the aluminum foil reserved for the negative electrode current collector for negative electrode charge transfer.

[0077] The electrolyte in the present invention includes a lithium salt, an organic solvent and optional additives. The types of the organic solvent, the lithium salt and the additives are not subject to specific restrictions and can be selected according to needs.

[0078] In a specific embodiment, the lithium salt includes but is not limited to LiPF6 (lithium hexafluorophosphate), LiBF4 (lithium tetrafluoroborate), LiClO4 (lithium perchlorate), LiFSI (lithium bis(fluorosulfonyl)imide), LiTFSI (lithium bis(trifluoromethanesulfonyl)imide), LiTFS (lithium trifluoromethanesulfonate), LiDFOB (lithium difluorooxalatoborate), LiBOB (lithium dioxalatoborate), LiPO2F2 (lithium difluorophosphate), LiDFOP (lithium difluorobis(oxalatophosphate)) and LiTFOP (lithium tetrafluorooxalatophosphate). At least one of them can be used alone or two or more can be used simultaneously.

[0079] In a specific embodiment, the organic solvent includes, but is not limited to, at least one of ethylene carbonate (EC), dimethyl carbonate (DMC), ethyl methyl carbonate (EMC), fluoroethylene carbonate (FEC), diethyl carbonate (DEC), butylene carbonate (BC), propylene carbonate (PC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), methyl formate (MF), methyl acetate (MA), ethyl acetate (EA), propyl acetate (PA), methyl propionate (MP), ethyl propionate (EP), propyl propionate (PP), methyl butyrate (MB), ethyl butyrate (EB), ethyl methyl sulfone (EMS), dimethyl sulfone (MSM), diethyl sulfone (ESE) and sulfolane (SF). The above organic solvents can be used alone or in combination of two or more.

[0080] In a specific embodiment, the additive may include a negative electrode film-forming additive, a positive electrode film-forming additive, and may also include an additive that can improve certain properties of the battery, such as an additive that improves the overcharge performance of the battery, an additive that improves the high temperature or low temperature performance of the battery, a flame retardant additive, etc. As an example, the additive includes but is not limited to fluoroethylene carbonate (FEC), vinylene carbonate (VC), vinyl carbonate (VEC), vinyl sulfate (DTD), propylene sulfate, vinyl sulfite (ES), 1,3-propane sultone (PS), 1,3-propylene sultone (PST), sulfonate cyclic quaternary ammonium salt, succinic anhydride, succinonitrile (SN), adiponitrile (AND), tris(trimethylsilyl) phosphate (TMSP), tris(trimethylsilyl) borate (TMSB). The electrolyte can be prepared according to conventional methods in the art. For example, an organic solvent, a lithium salt, and an optional additive can be mixed evenly in a set ratio to obtain an electrolyte. There is no particular restriction on the order of adding the materials. For example, lithium salt and optional additives are added to an organic solvent and mixed evenly to obtain an electrolyte; or, lithium salt is first added to an organic solvent, and then the optional additives are added to the organic solvent and mixed evenly to obtain an electrolyte.

[0081] The material of the diaphragm in the present invention can be selected from one or more of fibers, non-woven fabrics, polyethylene, polypropylene, and polyvinylidene fluoride, and the porous materials formed after processing. Optionally, the material of the diaphragm may include polyethylene or polypropylene. The diaphragm may be a substrate film or a composite film of a multilayer structure. When the diaphragm is a multilayer composite film, the materials of each layer are the same or different. For example, a ceramic coating, a glue layer, a metal oxide coating, etc. may also be provided on the isolation membrane.

[0082] The present invention will be described in further detail below in conjunction with specific embodiments. It should be understood that the following embodiments are only exemplary descriptions and explanations of the present invention and should not be construed as limiting the scope of protection of the present invention. All technologies implemented based on the above content of the present invention are included in the scope that the present invention is intended to protect.

[0083] Unless otherwise specified, the experimental methods used in the following examples are all conventional methods; the reagents, materials, etc. used in the following examples, unless otherwise specified, can be obtained from commercial channels.

[0084] In order to make the purpose, technical solutions and advantages of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below in combination with the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0085] Example 1

[0086] The lithium ion battery of the present invention is obtained by the following method:

[0087] (1) Preparation of positive electrode

[0088] Preparation of doped lithium cobalt oxide I: add 3000ppm of Al element, 1000ppm of Mg element, 1000ppm of Ti element and 800ppm of Zr element to the LCO precursor 9.6wt% of cobalt tetroxide and 90wt% of lithium carbonate, mix them evenly for use; compact the mixture with a bowl press, and then load the compacted mixture into a sagger; power on the kiln and adjust the temperature of the high temperature zone of the kiln to 800℃~1000℃, stack the saggers after loading and place them on the push plate of the push plate rack, and sinter them once for 15~20 hours; crush the compacted mixture after the first sintering to obtain the doped lithium cobalt oxide I of this embodiment;

[0089] Preparation of the first active material layer paste in the main area: add an appropriate amount of NMP to doped lithium cobalt oxide I at a ratio of 96.06wt% + carbon nanotubes at 2wt% + polyvinylidene fluoride at 1.94wt%, and stir thoroughly in a stirring tank to form a first active material layer slurry, which is recorded as Class 1 slurry.

[0090] Preparation of doped lithium cobalt oxide ⅠⅠ: Add 9.6wt% cobalt tetroxide and 90wt% lithium carbonate as LCO precursors, the doping amount of Al element is 1500ppm, the doping amount of Mg element is 500ppm, the doping amount of Ti element is 500ppm, and the doping amount of Zr element is 400ppm, and mix them evenly for use; compact the above mixture with a bowl press, and then load the compacted mixture into a sagger; after the kiln is powered on and the temperature of the high temperature zone of the kiln is adjusted to 800℃~1000℃, the saggers after being loaded are stacked and placed on the push plate of the outer push plate rack, and sintered for 15~20 hours; the compacted mixture after the first sintering is crushed to obtain the doped lithium cobalt oxide ⅠⅠ of this embodiment;

[0091] The doping amount of the above-mentioned doping elements in the second positive electrode active material layer is reduced by 50% compared with the doping amount in the first positive electrode active material layer;

[0092] Preparation method of the second active material layer paste of the passivation area: add appropriate amount of NMP to 90wt% of doped lithium cobalt oxide ⅠⅠ (Dv50 particle size is 10μm) + 1.2wt% of carbon nanotubes + 1.8wt% of polyvinylidene fluoride + 7wt% of alumina (filler, Dv50 particle size is 3μm), stir well in a stirring tank to prepare a second active material layer slurry, recorded as Class 2 slurry;

[0093] The ratio of the mass content of aluminum oxide in the second active material layer to the mass content of lithium cobalt oxide in the second active material layer is 0.078, and the ratio of the Dv50 particle size of aluminum oxide to the Dv50 particle size of the active material is 0.3.

[0094] Preparation of positive electrode sheet: The positive electrode sheet of the present invention is composed of a positive electrode current collector and a double-sided coating. An aluminum foil with a width of 100 mm and a length of 890 mm is used as the positive electrode current collector. A type 1 slurry with a length of 80 mm and a width of 68 mm is sequentially coated on the first and second surfaces of the aluminum foil along the length direction of the positive electrode current collector and dried to form a first active material layer. A type 2 slurry with a length of 6 mm and a width of 68 mm is dried to form a second active material layer. This is repeated many times. The coating length of the type 1 slurry is 80 mm and decreases by 2 mm each time. The coating length of the type 2 slurry is 6 mm and increases by 1 mm each time. When the coating length of the type 2 slurry is 10 mm, the coating is stopped. Then the slurry is calendered once by a roller pressing device until the compaction density is 4.05 g / cm 3 Cut off the 32mm empty foil at the edge in the width direction, weld the pole ear in the middle area, and stick the insulating tape to prepare a rolled positive electrode sheet. The cross-sectional SEM morphology of the first active material layer and the cross-sectional SEM morphology of the second active material layer of the positive electrode sheet are as follows: Figure 5 As shown, Figure 5 Figure a) is a cross-sectional SEM morphology of the first active material layer. Figure 5 Figure b) is a cross-sectional SEM morphology of the second active material layer; the planar SEM morphology of the second active material layer of the positive electrode sheet, such as Figure 6 shown.

[0095] (2) Preparation of negative electrode sheet

[0096] Preparation method of negative electrode slurry: Graphite, carbon nanotubes and styrene-butadiene rubber are mixed in a mass content ratio of 97wt%:1.1wt%:2.9wt%, and then a proper amount of deionized water is added and stirred thoroughly to obtain negative electrode slurry.

[0097] The preparation method of the negative electrode sheet of the present invention is as follows: a copper foil with a width of 100 mm and a length of 910 mm along the length direction of the negative electrode current collector is used as the negative electrode current collector, and the first and second surfaces of the copper foil are coated with the above-mentioned negative electrode slurry with a width of 60 mm and dried; the coating length is 910 mm. The negative electrode sheet is calendered once by a roller pressing device to a compaction density of 1.76 g / cm 3 Cut off the 40mm empty foil at the edge in the width direction, weld the pole ear in the middle empty foil area, and stick the insulating tape to prepare the rolled negative electrode sheet.

[0098] (3) Method for preparing a battery: Using the positive electrode sheet obtained in step (1), the negative electrode sheet obtained in step (2), and an isolation membrane and a non-aqueous electrolyte known in the industry, the lithium-ion battery is wound into a core according to the designed structure, and an appropriate amount of electrolyte is further added and the core is activated after secondary sealing to enable it to have charge and discharge capabilities, and then packaged to form the battery of this embodiment.

[0099] Example 2 Group

[0100] The preparation method of Example 2 is similar to that of Example 1, except that the Dv50 particle size of aluminum oxide in the preparation method of the second active material layer paste in the passivation region is changed. Specifically:

[0101] In Example 2-1, the Dv50 particle size of aluminum oxide is 0.5 μm, and the ratio of the Dv50 particle size of aluminum oxide to the Dv50 particle size of the positive electrode active material is 0.05;

[0102] In Example 2-2, the Dv50 particle size of aluminum oxide is 5 μm, and the ratio of the Dv50 particle size of aluminum oxide to the Dv50 particle size of the positive electrode active material is 0.5;

[0103] In Example 2-3, the Dv50 particle size of aluminum oxide is 10 μm, and the ratio of the Dv50 particle size of aluminum oxide to the Dv50 particle size of the positive electrode active material is 1;

[0104] In Example 2-4, the Dv50 particle size of aluminum oxide is 30 μm, and the ratio of the Dv50 particle size of aluminum oxide to the Dv50 particle size of the positive electrode active material is 3;

[0105] In Example 2-5, the Dv50 particle size of aluminum oxide is 0.3 μm, and the ratio of the Dv50 particle size of aluminum oxide to the Dv50 particle size of the positive electrode active material is 0.03;

[0106] In Example 2-6, the Dv50 particle size of aluminum oxide is 35 μm, and the ratio of the Dv50 particle size of aluminum oxide to the Dv50 particle size of the positive electrode active material is 3.5.

[0107] Example 3 Group

[0108] The preparation method of Example 3 is similar to that of Example 1, except that the mass content ratio of lithium cobalt oxide and aluminum oxide in the preparation method of the second active material layer paste in the passivation area is changed, specifically:

[0109] Example 3-1, lithium cobalt oxide is 95.8wt% and aluminum oxide is 1.2wt%. At this time, the mass content of aluminum oxide in the second active material layer and the mass content of lithium cobalt oxide in the second active material layer are 0.013;

[0110] Example 3-2, lithium cobalt oxide is 87.1wt% and aluminum oxide is 9.9wt%. At this time, the ratio of the mass content of aluminum oxide in the second active material layer to the mass content of lithium cobalt oxide in the second active material layer is 0.114;

[0111] In Example 3-3, the content of lithium cobaltate is 84 wt % and the content of aluminum oxide is 13 wt %. At this time, the ratio of the mass content of aluminum oxide in the second active material layer to the mass content of lithium cobaltate in the second active material layer is 0.155.

[0112] The relevant parameter settings of the above-mentioned Example 1, Example 2 group and Example 3 group are recorded in Table 1.

[0113] Table 1

[0114]

[0115] Example 4

[0116] The preparation method of Example 4 is similar to that of Example 1, except that the preparation method of the second active material layer paste in the passivation region is changed:

[0117] Preparation method of the second active material layer paste of the passivation area: add an appropriate amount of NMP to lithium cobalt oxide at a ratio of 97.03wt% + carbon nanotubes at 1wt% + polyvinylidene fluoride at 1.97wt%, and stir well in a stirring tank to prepare a second active material layer slurry;

[0118] The mass content ratio of the binder to the conductive agent in the first active material layer is a1=0.97; the mass content ratio of the binder to the conductive agent in the second active material layer is a2=1.97; a1 / a2=0.492.

[0119] Example 5 Group

[0120] The preparation method of Example 5 is similar to that of Example 4, except that the mass contents of the positive electrode active material, the conductive agent, and the binder in the preparation method of the second active material layer paste in the passivation region are changed, so that the mass content ratio a2 of the binder and the conductive agent in the second active material layer is changed:

[0121] Example 5-1, the mass content ratio of the binder and the conductive agent in the second active material layer is a2=1.51; a1 / a2=0.642;

[0122] Example 5-2, the mass content ratio of the binder and the conductive agent in the second active material layer is a2=5.59; a1 / a2=0.174;

[0123] In Example 5-3, the mass content ratio of the binder and the conductive agent in the second active material layer is a2=7.95; a1 / a2=0.122.

[0124] Example 6 Group

[0125] The preparation method of Example 6 is similar to that of Example 4, except that the mass contents of the positive electrode active material, the conductive agent, and the binder in the preparation method of the first active material layer paste in the passivation region are changed, so that the mass content ratio a1 of the binder and the conductive agent in the first active material layer is changed:

[0126] Example 6-1, the mass content ratio of the binder and the conductive agent in the first active material layer is a1=0.55; a1 / a2=0.279;

[0127] In Example 6-2, the mass content ratio of the binder to the conductive agent in the first active material layer is a1=1.55; a1 / a2=0.787.

[0128] The relevant parameter settings of the above-mentioned Example 4, Example 5 group and Example 6 group are recorded in Table 2.

[0129] Table 2

[0130]

[0131]

[0132] Example 7 Group

[0133] The preparation method of Example 7 is similar to that of Example 1, except that the doping amount of lithium cobalt oxide in the preparation method of the second active material layer paste in the passivation region is changed, specifically:

[0134] Example 7-1: Preparation of doped lithium cobalt oxide ⅠⅠ: the doping amount of Al element is 2700ppm, the doping amount of Mg element is 900ppm, the doping amount of Ti element is 900ppm, and the doping amount of Zr element is 720ppm;

[0135] The doping amount of the above-mentioned doping elements in the second positive electrode active material layer is 10% lower than the doping amount in the first positive electrode active material layer;

[0136] Example 7-2: Preparation of doped lithium cobalt oxide ⅠⅠ: the doping amount of Al element is 1200ppm, the doping amount of Mg element is 400ppm, the doping amount of Ti element is 400ppm, and the doping amount of Zr element is 320ppm;

[0137] The doping amount of the above-mentioned doping elements in the second positive electrode active material layer is reduced by 60% compared with the doping amount in the first positive electrode active material layer.

[0138] Example 7-3: Preparation of doped lithium cobalt oxide ⅠⅠ: the doping amount of Al element is 2850ppm, the doping amount of Mg element is 950ppm, the doping amount of Ti element is 950ppm, and the doping amount of Zr element is 760ppm;

[0139] The doping amount of the above-mentioned doping elements in the second positive electrode active material layer is 5% lower than the doping amount in the first positive electrode active material layer.

[0140] Comparative Example 1

[0141] The preparation method of Comparative Example 1 is similar to that of Example 1, except that the preparation method of the positive electrode sheet is changed:

[0142] Aluminum foil with a width of 100 mm and a length of 890 mm was used as the positive electrode current collector. Type 1 slurry with a width of 60 mm and a length of 890 mm was coated on the first and second surfaces of the aluminum foil and dried. The aluminum foil was calendered once with a roller press to a compaction density of 4.05 g / cm 3 The 40 mm edge of the empty foil in the width direction is cut off, and the pole ear is welded in the middle empty foil area, and an insulating tape is attached to prepare a rolled conventional positive electrode sheet.

[0143] Test Case

[0144] The batteries prepared in the above examples and comparative examples were subjected to the following tests:

[0145] (1) Charge transfer impedance (Rct) test of the first active material coating and the second active material coating:

[0146] The test method is to disassemble the battery prepared in the above embodiments and comparative examples at 50% SOC after formation to obtain the positive electrode sheet, and use a slicer to cut the main area and passivation area of ​​the positive electrode sheet into 1 cm square pieces, and reserve the pole ears. The main area and the positive electrode are assembled into a monolithic battery 1 to 1, and the passivation area is assembled into a monolithic battery 1 to 1, and 0.5g of electrolyte is injected, and it is packaged into a soft-package monolithic symmetrical battery. The symmetrical battery is placed on a Zahner electrochemical workstation for measurement, and the measurement frequency is 50mHz to 200MHz. After the test, the data is fitted by an equivalent circuit and the Rct impedance values ​​of the main area and the passivation area are read, that is, the Rct impedance of the first active material coating and the Rct impedance of the second active material coating, in mΩ.

[0147] (3) Battery charge and discharge capacity retention rate test:

[0148] Test method: The full batteries prepared in the above embodiments and comparative examples were cycled for 800T on a blue-power test system under a 3C step-charge regime, and the charge and discharge capacity retention rate (%) of the battery was calculated.

[0149] (4) Battery cycle expansion rate test:

[0150] Test method: Place the full battery prepared in the above-mentioned embodiments and comparative examples under the PPG test equipment for 1000T cycles, record the thickness of the upper battery, and calculate the cycle expansion rate (%) of the battery.

[0151] Table 2

[0152]

[0153] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.

Claims

1. A battery, characterized in that: An electrode assembly comprising a winding structure, the electrode assembly comprising a negative electrode sheet, a separator and a positive electrode sheet stacked and wound in sequence, the electrode assembly comprising an arc region and a straight region connected to the arc region, the positive electrode sheet comprising a positive electrode collector, the positive electrode collector being provided with a main region and a passivation region along a length direction, the passivation region being located in the arc region, and the main region being located in the straight region; At least one side surface of the positive electrode current collector located in the main region includes a first active material layer, and at least one side surface of the positive electrode current collector located in the passivation region includes a second active material layer; The impedance of the first active material layer is smaller than the impedance of the second active material layer.

2. The battery according to claim 1, wherein The passivation region includes N 钝 Sub-passivation area, N 钝 = the total number of arcs of the electrode assembly winding structure formed by winding the positive electrode sheet; At least one side surface of the positive electrode current collector located in the sub-passivation region includes the second active material layer, or at least one side surface of the positive electrode current collector located in the sub-passivation region includes the first active material layer and the second active material layer.

3. The battery according to claim 2, wherein In any one of the sub-passivation regions, along the length direction of the positive electrode current collector, the length of the second active material layer is L, the circumference of the arc formed by the sub-passivation region corresponding to the second active material layer is C, and L and C satisfy 1 / 3*C≤L≤1 / 2*C; And / or, along the width direction of the positive electrode current collector, the width of the second active material layer is D 活 , the width of the positive electrode sheet is D 极 , the D 活 and D 极 , satisfying D 活 ≤D 极 ; And / or, along the length direction of the positive electrode current collector, the distance between adjacent second active material layers is I, and the width of the straight area is D 平 , the width of the arc area is D 圆 , the I and D 平 and D 圆 , satisfying 0≤ID 平 ≤D 圆 .

4. The battery according to claim 1 or 2, wherein The coverage area of ​​the second active material layer on the surface of the positive electrode current collector accounts for 3%-20% of the total area of ​​the positive electrode current collector; preferably 3%-8%.

5. The battery according to claim 1, wherein The first active material layer and the second active material layer include a positive electrode active material, a binder and a conductive agent; The mass content ratio of the binder to the conductive agent in the first active material layer is a1, 0.5≤a1≤2; The mass content ratio of the binder and the conductive agent in the second active material layer is a2, 1.5≤a2≤6; Preferably, 0.13≤a1 / a2≤0.

6.

6. The battery according to claim 5, wherein The mass content of the positive electrode active material in the second active material layer is 90wt%-98wt%, the mass content of the binder in the second active material layer is 2wt%-10wt%, and the mass content of the conductive agent in the second active material layer is 0.1wt%-1wt%; And / or, the mass content of the positive electrode active material in the first active material layer is 90wt%-98wt%, the mass content of the binder in the first active material layer is 1wt%-5wt%, and the mass content of the conductive agent in the first active material layer is 0.5wt%-5wt%.

7. The battery according to claim 1, wherein The first active material layer includes a positive electrode active material, a binder and a conductive agent, and the second active material layer includes a positive electrode active material, a filler, a binder and a conductive agent; Preferably, the filler comprises inorganic particles, and the inorganic particles comprise at least one of oxide ceramics, nitride ceramics, and carbide ceramics; Preferably, the Dv50 particle size of the inorganic particles is 0.5 μm-30 μm; preferably 0.5 μm-5 μm; Preferably, the ratio of the Dv50 particle size of the inorganic particles to the Dv50 particle size of the positive electrode active material is 0.05-1.

8. The battery according to claim 7, wherein The ratio of the mass content of the filler in the second active material layer to the mass content of the positive electrode active material in the second active material layer is 0.01-0.11; Preferably, the mass content of the positive electrode active material in the second active material layer is 90wt%-97wt%, the mass content of the filler in the second active material layer is 1wt%-11wt%, the mass content of the binder in the second active material layer is 1wt%-5wt%, and the mass content of the conductive agent in the second active material layer is 0.5wt%-5wt%; Preferably, the mass content of the positive electrode active material in the first active material layer is 90wt%-98wt%, the mass content of the binder in the first active material layer is 1wt%-5wt%, and the mass content of the conductive agent in the first active material layer is 0.5wt%-5wt%.

9. The battery according to claim 7, wherein The ratio of the specific surface area of ​​the second active material layer to the specific surface area of ​​the first active material layer is 3-10; Preferably, the specific surface area of ​​the first active material layer is 0.1 m 2 / g-0.3m 2 / g, the specific surface area of ​​the second active material layer is 0.5m 2 / g-3m 2 / g.

10. The battery according to claim 1, wherein The first active material layer and the second active material layer contain doping elements, and the doping elements include at least one of Al, Mg, Ti, and Zr; Preferably, in the first active material layer, the doping elements include Al, Mg, Ti and Zr, the doping amount of Al element is 1000ppm-5000ppm, the doping amount of Mg element is 600ppm-2000ppm, the doping amount of Ti element is 600ppm-2000ppm, and the doping amount of Zr element is 500ppm-1000ppm; Preferably, in the second active material layer, the doping elements include Al, Mg, Ti and Zr, the doping amount of Al element is 500ppm-2000ppm, the doping amount of Mg element is 200ppm-1000ppm, the doping amount of Ti element is 100ppm-500ppm, and the doping amount of Zr element is 100ppm-500ppm; Preferably, the doping amount of the doping element in the second active material layer is reduced by 10%-50% compared with the doping amount of the doping element in the first active material layer.

Citation Information

Patent Citations

  • Battery cell

    CN114447280A

  • Electrode assembly and electrochemical device and electronic device comprising same

    CN114759272A

  • Electrochemical device and electronic device

    CN117546334A

  • Positive plate and battery

    CN221900036U

  • Electrode assembly, battery cell, battery and electric device

    WO2024020775A1